Developing Writing Skills through English Short Stories: A Case Study in the Classroom: English Writing Skills - Kottacheruvu, Nagendra (International Journal of Language and Literary Studies, 2023)
This study seeks to determine the efficacy and utility of teaching writing skills through short stories to third-semester postgraduate students whose native language and language of instruction is Urdu at Maulana Azad National Urdu University in Hyderabad, India. This article investigates primarily the extent to which selected English short stories are useful and effective for teaching English writing skills. Due to their Urdu-influenced origins, it is a fact that the majority of our students struggle to speak and write in English. Due to their socio-cultural, fiscal, and pedagogical circumstances, as well as the way they are taught, they rarely interact with the target language. They are always hesitant to speak and write in the target language due to fear, hesitancy, and lack of experience, despite their passion for learning English. Mastering writing is regarded as one of the most transferable skills because it requires an extensive vocabulary and correct grammar. In addition, it requires constant effort, practise, reading, and exposure to language use. Students from both Madarasa and Urdu backgrounds with little exposure and practise find mastering writing to be the most challenging endeavour. The findings of this study indicate that reading English short stories improves writing skills.